Emerging miniaturized technologies for airborne particulate matter pervasive monitoring. (April 2017) - Carminati, Marco; Ferrari, Giorgio; Sampietro, Marco
Highlights: A new monitoring paradigm based on distributed participatory sensing is emerging. Novel solid-state technologies for low-cost, compact dust monitoring are reviewed. AttoFarad micro-capacitive technique has demonstrated to achieve 10 μm resolution. Miniaturization will foster the integration of such sensors inside smartphones. Abstract: In order to address the increasing demand for real-time and pervasive monitoring of air quality and, in particular, of particulate matter, novel solid-state sensor technologies and compact instrumentation for dust detection have been recently proposed. Within the context of distributed dust monitoring in urban areas, we briefly review the most recent advances in miniaturized optical, mass-sensitive and capacitive approaches based on solid-state technologies for the detection of micrometric and nanometric airborne particles. Different application scenarios (spanning from dense wireless networks in smart-cities, composed of several fixed or mobile nodes, to pocket-sized personal dosimeters) are also discussed. New participatory and ubiquitous monitoring and mapping strategies are presented, being enabled by the embedment of these ultra-miniaturized sensors in handheld mobile devices, such as smartphones, already integrating several MEMS sensors.